Histopathological Evaluation of Chronic Rhinosinusitis: A Critical Review. Issue 5 (September 2013) - Jiang, Nancy; Kern, Robert C.; Altman, Kenneth W.
Background: Chronic rhinosinusitis (CRS) consists of a constellation of symptoms, including facial pressure/pain, hyposmia, rhinorrhea, and nasal congestion. On histopathological evaluation, the disease can be divided into pathophysiologically distinct subgroups. This study systematically reviews the literature regarding the unique histopathological findings of the various subtypes of CRS to determine the potential diagnostic value of performing tissue analysis of CRS specimens beyond routine hematoxylin and eosin (H&E) staining. Methods: A PubMed search was untaken to identify articles that evaluated the histopathological features of CRS. Six hundred fifty-four relevant articles were identified and after application of specific exclusion criteria, 71 articles were further reviewed in detail. Results: All articles included analysis of tissue samples from in-office biopsies or intraoperative specimens of patients who underwent sinus surgery. CRS was often further divided into subgroups and compared with each other and with a control group. The subgroups included CRS with and without nasal polyps, asthmatic and nonasthmatic patients, and with and without eosinophilia. Distinct inflammatory mediators were found for the different subgroups. Twenty-eight articles evaluated these inflammatory markers for their potential value as prognostic indicators. Conclusion: CRS is a heterogeneous disease based on its histopathological findings. Information that is obtainable from light microscopy, but typically goes unreported, can serve as valuable prognostic indictors. However, routine H&E staining is suboptimal in distinguishing among the various subgroups of CRS. Assessment of specific inflammatory mediators in sinus mucosa specimens may help provide prognostic information and guide more tailored treatment for the individual patient.